Video Game Play Effects on Dreams: Self-Evaluation and Content Analysis - Gackenbach, Jayne Isabel; Kuruvilla, Beena (Eludamos: Journal for Computer Game Culture, 2008)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Times; panose-1:2 2 6 3 5 4 5 2 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:536902279 -2147483648 8 0 511 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:12.0pt; margin-left:0cm; text-align:justify; line-height:14.0pt; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:Arial; mso-fareast-font-family:Times; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Recent dreams were collected over a year’s period from college undergraduates. In addition to providing self-evaluations of the dreams, participants were also asked to answer a variety of media use questions. These were both in terms of their media use the day before the dream and in terms of their historical media use with the most interactive and absorbing media available today, video games. High-end gamers’ dreams were content-analyzed using the Hall and Van de Castle system. These were compared to dreams from a similar population that were collected by interview but were not necessarily recent. There was some replication and some differences in these two different dream samples from individuals with the same gamer history. The second analysis examined day before electronic media use more specifically by loading all the gamer history and media use information with two types of dream variables: sum scores from the Hall and Van de Castle scale and self-evaluations of the dream. Seven of nine factors loaded some combination of media and dream content. This study further supports the idea that general electronic media use and game play in particular are affecting how we process and store information by demonstrating changes at the source of such processes, in dreams.